(untitled) (Bangladesh Journal of Pathology, 2009)
A 60 year old male presented with pulmonary tuberculosis and moderate anaemia. He was on antitubercular treatment and haematinics. The anaemia remained refractory to treatment. But the patient developed recurrent deep vein thrombosis and pancytopenia, which subsequently transformed into acute myeloid leukemia (AML).The development of AML suggested that the haematological aberrations observed earlier were actually states of myelodysplastic syndrome (MDS). The significance of concurrently developing AML and MDS is discussed and reported here. doi: 10.3329/bjpath.v24i1.2879 Bangladesh J Pathol 24 (1) : 25-27